2019
DOI: 10.1101/706978
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Motor Output Matters: Evidence of a Continuous Relationship Between Stop/No-go P300 Amplitude and Response Force on Failed Inhibitions at the Trial-Level

Abstract: Motor actions can be suppressed with varying degrees of success, but this variability is not often captured in traditional experiments where inhibitory-control is conceptualised as an all-or-none process. Although the Stop/No-go P300 (a frontocentral positivity in the event-related potential (ERP) occurring around 300 ms after a Stop/No-go stimulus) has been implicated as a measure of inhibitory-control, it is unclear how the range of motor outputs relates to the P300. We examined the nature of this associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…Our results have several important implications. First, whereas several earlier studies of action-stopping recorded partial EMG for various purposes (De Jong et al, 1990;Mcgarry et al, 2000;McGarry and Franks, 1997), some more recent ones specifically interpreted the time of the partial EMG as related to stopping (Huster et al, 2019;Nguyen et al, 2019;Raud et al, 2019;Raud and Huster, 2017;Thunberg et al, 2019). Our results strongly affirm that partial EMG can be used to estimate the latency of stopping reflected in the muscle.…”
Section: Discussionsupporting
confidence: 75%
“…Our results have several important implications. First, whereas several earlier studies of action-stopping recorded partial EMG for various purposes (De Jong et al, 1990;Mcgarry et al, 2000;McGarry and Franks, 1997), some more recent ones specifically interpreted the time of the partial EMG as related to stopping (Huster et al, 2019;Nguyen et al, 2019;Raud et al, 2019;Raud and Huster, 2017;Thunberg et al, 2019). Our results strongly affirm that partial EMG can be used to estimate the latency of stopping reflected in the muscle.…”
Section: Discussionsupporting
confidence: 75%
“…Wessel (2018) demonstrated that the requirement to inhibit highly prepotent responses, elicited by infrequent NoGo signals, led to greater P3 amplitude. Moreover, Nguyen et al (2019) observed that P3 amplitude scaled with force measurements during failed stopping, so that smaller P3s were associated with greater force (and therefore greater response error). The P3's links to the motor system have been further corroborated in a study by Hynd et al (2020), which demonstrated that P3 amplitude relates to inhibitory GABA activity in motor cortex: subjects with higher levels of inhibitory GABAa activity (measured using short-interval intracortical inhibition) showed larger and earlier P3 ERPs following stop signals.…”
Section: 24mentioning
confidence: 96%
“…Various studies have been conducted in the conformation of the No Return Point hypothesis, which most were in laboratory conditions (13)(14)(15)(16)(17)(18)(19). Gao and Zelaznik (20) evaluated Henry and Harrison's hypothesis in detail.…”
Section: Introductionmentioning
confidence: 99%